Role of transcription factors in apoptotic cells clearance - Gao, Yuqiong; Jiao, Yating; Gong, Xiaoyi; Liu, Jie; Xiao, Hui; Zheng, Qian (Frontiers in Cell and Developmental Biology, 2023)
The human body generates 10–100 billion cells every day, and the same number of cells die to maintain homeostasis. The genetically controlled, autonomously ordered cell death mainly proceeds by apoptosis. Apoptosis is an important way of programmed cell death in multicellular organisms, timely and effective elimination of apoptotic cells plays a key role in the growth and development of organisms and the maintenance of homeostasis. During the clearance of apoptotic cells, transcription factors bind to specific target promoters and act as activators or repressors to regulate multiple genes expression, how transcription factors regulate apoptosis is an important and poorly understood aspect of normal development. This paper summarizes the regulatory mechanisms of transcription factors in the clearance of apoptotic cells to date.